Sistem Kendali Ayunan Bayi Berbasis Mikrokontroller dan Android - Abdullah, Ahmad; Zainuddin, Zahir; Achmad, Andani (Journal of System and Computer Engineering, 2023)
This study aims to design a prototype of a microcontroller and arduino-based baby swing control system that will be very useful for housewives who have babies. This system will automatically work to move the swing when the sound of a baby and water is detected. This system is designed using a sound sensor that functions to detect the baby's voice, a water sensor to detect water when a baby is urinating, a DC motor that functions to move the swing automatically and a mobile application that functions to monitor swings. The test results show that the tool functions as desired, where when the tool detects the sound of a baby's cry, the tool automatically moves the swing, when the tool detects the presence of water, the swing will send a notification to the smartphone, this tool also successfully displays information to the smartphone in the form of a state baby in the form of video and sensor conditions on the swing. The communication distance between the smartphone and the device is 20 meters.